Self-Efficacy Analysis on Sugar Levels in Diabetes Mellitus Patients: Literature Review - Siti Meltiana Kase; Sandu Siyoto (PT. Griya Eka Sejahtera, 2021)
Background: Problems that arise related to DM such as changes in the way of life such as feeling lonely and aware of death, living alone, changes in economic terms, chronic diseases, weakening physical strength so that sufferers experience decreased body functions, so the need for self-efficacy and regular checks of levels blood sugar. Method: The literature is sourced from the google scholar database, google scholar published from 2015 to 2019, and manually selects articles that are relevant to the research question. Results: The results of the study in a literature review revealed that the majority of respondents had self-efficacy in the good category with blood sugar levels in the normal category. The results showed that type 2 diabetes mellitus is the most common type of DM, which is 90-95% of all DM patients and is mostly experienced by adults over 40 years of age. This is due to insulin retention tends to increase in the elderly (40-65 years).. Conclusion: Self-efficacy has an important role in changing these behaviors where there must be confidence and awareness that you have the ability to take the expected actions in this case the patient's behavior in controlling blood sugar levels